Effects of extensive reading circles on lower proficiency tertiary level ESL learners' oral communicative competence - Baharuddin Marji, Aliyah (2016)
The purpose of this study was to investigate the effects of extensive reading circles on ESL learners’ oral communicative competence at a local institution of higher learning. The study used a non-equivalent control group pre-test-posttest quasi experimental design. Two intact classes out of seven were identified as subjects of the study. The intact classes consisted of Year 2 students (N=47) enrolled for a course in oral proficiency and they were the subjects of the study over a period of 14 weeks. The intact classes were randomly assigned into the experimental (N=27) and control (N=20) groups. Data was collected by means of pre-test and post test scores using the following instruments specifically an oral production interview, a language proficiency test and five questionnaires for both the control and experimental group. At the end of the treatment, subjects in the experimental group were observed and scored during the post oral interview and tested on the same proficiency test to determine the effects of extensive reading circles in two conditions. Subjects were further evaluated on their oral communicative competence using two assessment methods. The quantitative method included an analytical scoring scale as a measurement for evaluating five dimensions of oral competency (comprehensibility, fluency of speech, vocabulary usage, grammar and syntax and pronunciation). The qualitative analysis included class observation using an analytical scale as a measurement for evaluating three dimensions of communicative competence (content, communication skills and English skills) and the assessment of subjects’ transcribed data obtained during cooperative discussions. Both methods were used to determine the effects of extensive reading on promoting subjects’ critical, analytical and creative thinking that influenced their oral communicative performance during discussions. The study revealed that the experimental group had shown more significant results statistically over the control group with medium and large effect sizes. This demonstrates that extensive reading reflects a social activity that can effectively promote communicative language learning. It also demonstrates that employing cooperative learning activities as opposed to solitary language learning allowed learners to apply the knowledge of the language gained through extensive reading in an authentic stress free environment. The findings of the study confirmed the comprehensible input hypothesis theory and the principles underlying extensive reading and cooperative learning for oral communicative competence.